10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Humanitarian crises disrupt the continuous care required for non-communicable diseases (NCDs), yet evidence on effective health-system responses remains fragmented. We conducted a scoping review, reported in accordance with PRISMA-ScR, to map health-system challenges, implemented and recommended strategies, resilience functions, and evidence gaps for cardiovascular diseases, diabetes, cancer, and chronic respiratory diseases in humanitarian settings. PubMed/MEDLINE, Scopus, Web of Science, relevant organizational websites, and reference lists were searched. English-language empirical studies, reviews, programme reports, guidelines, policy documents, and operational frameworks addressing continuity of NCD care during crises were eligible. Evidence was synthesized across nine operational domains and characterized according to patient or clinical outcomes, service or implementation outcomes, descriptive or recommendation-only evidence, and economic information. Thirty-seven sources published between 2013 and 2025 were included. Country-specific empirical evidence was concentrated in Asia and the Middle East. Service delivery had the strongest outcome-based evidence, whereas financing, coordination, governance, and transformative system reforms were supported mainly by descriptive or recommendation-based sources. No full comparative economic evaluation was identified. Reported challenges involved disrupted access and referral, failures of medicines and infrastructure, workforce and information constraints, and financial and social barriers. Implemented strategies included integrated primary care, mobile and telemedicine services, structured follow-up, medicine-continuity measures, electronic monitoring, and community and workforce interventions. Empirical evidence predominantly addressed absorptive and adaptive responses; transformative strategies were mainly proposed in guidance and policy documents and were rarely evaluated. Three cross-cutting priorities emerged from the synthesis: a minimum emergency NCD service and medicine package; continuity mechanisms for patients at highest risk from treatment interruption; and simplified, integrated NCD care within emergency and primary-care services. Future research should prospectively evaluate these priorities using standardized implementation, clinical, equity, and economic indicators and should involve affected communities and frontline practitioners in intervention design and assessment.